Біоекологічні особливості Echinacea pallida Nutt. у Лісостепу України - Porada, A.A. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2006)
Bioecological peculiarities of growing and develop ment of Echinacea pallida Nutt. and methods of reproduction are studed. The best sample of Echinacea pallida according to biologically and economically valuable properties was selected. This species was received from Canada.